2017
DOI: 10.1016/j.ejps.2017.01.029
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobin-nanofibrillated cellulose stabilized emulsions for encapsulation and release of BCS class II drugs

Abstract: The purpose of this study was to construct biopolymer-based oil-in-water emulsion formulations for encapsulation and release of poorly water soluble model compounds naproxen and ibuprofen. Class II hydrophobin protein HFBII from Trichoderma reesei was used as a surfactant to stabilize the oil/water interfaces of the emulsion droplets in the continuous aqueous phase. Nanofibrillated cellulose (NFC) was used as a viscosity modifier to further stabilize the emulsions and encapsulate protein coated oil droplets in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…The plant derived native nanofibrillar cellulose (NFC) hydrogel, GrowDex®, provides a wellcharacterized and defined matrix [17,25] . This hydrogel is easy to handle and is biocompatible with human cells, whilst also allowing the simple retrieval of cells from the scaffold for further use [25,26]. Although the immunogenicity of plant-derived NFC is still under investigation, the low immune response to other plant derived hydrogels has been reported [27] [12,28].…”
Section: Discussionmentioning
confidence: 99%
“…The plant derived native nanofibrillar cellulose (NFC) hydrogel, GrowDex®, provides a wellcharacterized and defined matrix [17,25] . This hydrogel is easy to handle and is biocompatible with human cells, whilst also allowing the simple retrieval of cells from the scaffold for further use [25,26]. Although the immunogenicity of plant-derived NFC is still under investigation, the low immune response to other plant derived hydrogels has been reported [27] [12,28].…”
Section: Discussionmentioning
confidence: 99%
“…5 ) prepared with nanoprecipitation method. Till date hydrophobin׳s use as a stabilizing agent is reported only for the topical and oral nanosuspensions, that leaves a lot of room for expanding its horizons for parenteral administration, provided suitable toxicity are generated first 90 , 91 .
Figure 5 TEM images showing beclomethasone dipropionate (BDP) precipitation in deionized water (A) without class II hydrophobin (HFBII), (B) with 0.005% HFBII, (C) with 0.05% HFBII, and (D) with 0.1% HFBII (Scale bar: 0.5 µm).
…”
Section: Parenteral Nanosuspensionmentioning
confidence: 99%
“…Given their high surface activity, hydrophobin-based drug stabilization has been an area of active research [3742]. Valo et al demonstrated the preparation of class II hydrophobin-coated drug nanoparticles below 200 nm that were stable for at least 5 h in suspension, and for longer times after freeze-drying [37].…”
Section: Applicationsmentioning
confidence: 99%
“…They showed that the formulation was biocompatible and exhibited a high drug loading, high nanoparticle yield, small particles of narrow distribution, and delayed drug release in rats [41]. Moreover, the effective stabilization of model drug oil-in-water emulsions using low concentrations of HFBII with nanofibrillar cellulose suggests an additional advantage of formulation with hydrophobins since less material is needed compared to traditional pharmaceutical surfactant-based emulsion stabilizers [42]. When the class I hydrophobin SC3 was used to solubilize the hydrophobic drugs cyclosporine A and nifedipine, the oral bioavailability was increased by 2- and 6-fold, respectively [44].…”
Section: Applicationsmentioning
confidence: 99%